Translation of artemether-lumefantrine treatment policy into paediatric clinical practice: an early experience from Kenya. - Zurovac, D; Njogu, J; Akhwale, W; Hamer, D; Snow, R (2008)
OBJECTIVE: To describe the quality of outpatient paediatric malaria case-management approximately 4-6 months after artemether-lumefantrine (AL) replaced sulfadoxine-pyrimethamine (SP) as the nationally recommended first-line therapy in Kenya. METHODS: Cross-sectional survey at all government facilities in four Kenyan districts. Main outcome measures were health facility and health worker readiness to implement AL policy; quality of antimalarial prescribing, counselling and drug dispensing in comparison with national guidelines; and factors influencing AL prescribing for treatment of uncomplicated malaria in under-fives. RESULTS: We evaluated 193 facilities, 227 health workers and 1533 sick-child consultations. Health facility and health worker readiness was variable: 89% of facilities stocked AL, 55% of health workers had access to guidelines, 46% received in-service training on AL and only 1% of facilities had AL wall charts. Of 940 children who needed AL treatment, AL was prescribed for 26%, amodiaquine for 39%, SP for 4%, various other antimalarials for 8% and 23% of children left the facility without any antimalarial prescribed. When AL was prescribed, 92% of children were prescribed correct weight-specific dose. AL dispensing and counselling tasks were variably performed. Higher health worker's cadre, in-service training including AL use, positive malaria test, main complaint of fever and high temperature were associated with better prescribing. CONCLUSIONS: Changes in clinical practices at the point of care might take longer than anticipated. Delivery of successful interventions and their scaling up to increase coverage are important during this process; however, this should be accompanied by rigorous research evaluations, corrective actions on existing interventions and testing cost-effectiveness of novel interventions capable of improving and maintaining health worker performance and health systems to deliver artemisinin-based combination therapy in Africa.